1984
DOI: 10.1093/ajcn/40.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol, β-sitosterol, and stigmasterol

Abstract: Cholesterol and fat are implicated as dietary factors enhancing the risk for colon carcinogenesis. Plant sterols such as beta-sitosterol when added to diets of experimental animals treated with colon carcinogens reduce tumor yields and counteract the proliferative changes associated with carcinogenesis. The question of whether the diet of human populations at low risk for colon cancer is mirrored in their sterol composition is addressed in this study. Four study groups consisting of 18 Seventh-day Adventist (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Our results suggest that phytosterols are bioactive in their natural food matrices and in amounts (around 500 mg/day) that can be readily achieved in the diet without supplementation (Nair et al 1984, Ostlund 2002, Racette et al 2009). We could not attribute the cholesterol metabolic differences to differences in macronutrients, cholesterol, fat quality, vitamins or minerals.…”
Section: Discussionmentioning
confidence: 79%
“…Our results suggest that phytosterols are bioactive in their natural food matrices and in amounts (around 500 mg/day) that can be readily achieved in the diet without supplementation (Nair et al 1984, Ostlund 2002, Racette et al 2009). We could not attribute the cholesterol metabolic differences to differences in macronutrients, cholesterol, fat quality, vitamins or minerals.…”
Section: Discussionmentioning
confidence: 79%
“…The health benefits of β ‐sitosterol have recently been reported in several studies which refer mainly to cholesterol levels being reduced due to the inhibition of absorption in the intestinal tract. Several studies have shown that consuming β ‐sitosterol inhibits the development of chemically induced cancers, such as colon, prostate and breast cancers . Furthermore, phytosterols, especially β ‐sitosterol, exhibit significant anti‐inflammatory effects .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, case-control work by De Stefani [41] assessing the effects of PS on stomach cancer risk showed an odds ratio of 0.33 (95% CI 0.17–0.65) among those with the highest PS intake. Populations such as Seventh Day Adventists, who have a lower cancer risk that that of the general population, have likewise been found to have greater intakes of PS [42]. While limited, epidemiological data suggests a correlation between plant sterol intake and a reduction in cancer risk.…”
Section: Plant Sterols and Cancermentioning
confidence: 99%